Leadership and personal development : a toolbox for the 21st century professional - Kruckeberg, Katja; Amann, Wolfgang; Green, Mike, 1959- (Information Age Pub., 2011)
An attempt to equip you with new levels of thinking and new skill sets to make you more successful at leading and developing yourself and others in a variety of contexts. With structured activities and proven techniques from people who have successfully applied the lessons found in this book, Leadership and Personal Development, you will be armed with an effective approach to development.